Criteria for limited sanity for individuals that committed a sexual assault - Kozerackaya, Elena (Psychosomatic Medicine and General Practice, 2018)
Background. The results of scientific research conducted within the framework of the doctoral thesis "Forensic psychiatric evaluation of persons who have committed sexual criminal offenses". Purpose. The research aimed to develop criteria for a forensic psychiatric assessment of individuals (suspects, accused persons), who have committed sexual assault, with the selection of the group with "limited sanity". It was based on the study of clinical and pathopsychological, socio-demographic patterns of mental disorders, using the method of situational analysis. Materials. For this study the author analyzed 286 cases of forensic psychiatric examinations regarding the subject, those committed the sexual offense and were at the forensic psychiatric examination in Kyiv city center forensic psychiatric examination from 2000 to 2016 (16 years). Objective. To determine the relationship between the degree of opportunities, to realize their actions and manage the solutions and expert author on the group - "responsibility" - was empirically selected group - "limited responsibility", which was formed artificially, based on the national concept of "limited responsibility". Results. To determine the connection between the degree of the ability to realize one’s actions and to govern them and the decision of expert questions, all the observations were divided into two comparison groups. Diagnostics of paraphilia, determination of its forms and types were carried out according to the criteria for the diagnostics used in ICD-10, as well as definitions adopted in Ukrainian psychiatry. Sexual deviation and various forms of unusual sexual interests from generally accepted as part of the ethnic-cultural forms of sexual behavior. Conclusions. Results revealed that the identified socio-demographic and clinical data in this scientific research can be determined by the criteria "limited responsibility" in forensic psychiatric examinations of persons who have committed sexual offenses. Consequently, these groups are heterogeneous whether examinee was intoxicated during the SDA or not the "limited sanity" of sexual assault is warranted.